Rediseño del perfil consultor para el módulo de expedientes del sistema “Cobros & Coactivo” de la unidad Administrativa especial de gestión pensional y contribuciones parafiscales de la protección social - UGPP (2021)
Currently, the Collections Sub-Directorate of the Special Administrative Unit for Pension Management and Social Protection Parafiscal Contributions - UGPP in order to fulfill its functions of coordinating, developing and supervising the persuasive and coercive or executive collection processes, is requires knowing the information of the natural or legal persons that They are reported to the entity for non-compliance with their pension and parafiscal payments. For this, the entity has a system called "Collections & Coercive", which contains the historical information of the records of the collection processes carried out by the Unit directly.